Gestión del talento humano y su incidencia en el servicio al cliente en la empresa Municipal de cementerio del cantón Quevedo año 2012.Quevedo - Moncayo Carreño, Marcel Daniel (2015)
This research work is carried out with the purpose of analyzing the processes of the management of human talent with an emphasis on customer service received by users of the organization, sought to identify and check the processes of selection and recruitment of its staff. The research work consists of a part or documentary theory and practice, consisting of two segments, the first corresponds to the introductory part and the second to the chapters in a number of seven constitute the body of the document. It is also considered by documentary that his objective was achieved with the application of theories or general order proposals already existing, in order to achieve this objective, is obtained it from the reality that is the organization with their servers, users, and the manager of the company of municipal cemeteries of the Quevedo City……